CARDIOMETABOLIC RISK AND MODERN METHODS OF ITS CORRECTION IN PREGNANT WOMEN WITH CHRONIC ARTERIAL HYPERTENSION - A. V. Padyganova; A. V. Padyganova (Российский кардиологический журнал, 2012)
Aim. To assess the effects of antihypertensive therapy on the dynamics of cardiometabolic risk factors among pregnant women with chronic arterial hypertension (AH) in the second trimester. Material and methods. In total, 37 pregnant women with chronic AH were examined. The clinical and anamnestic data were analysed, and the levels of office blood pressure, body mass index, blood lipids, systemic inflammation markers (C-reactive protein, fibrinogen), and glucose were measured. Subclinical pathology of target organs was assessed via the measurement of left ventricular myocardial mass index (echocardiography), glomerular filtration rate, and microalbuminuria. Results. Slow-release nifedipine therapy improved the parameters of lipid metabolism and target organ status. Metoprolol therapy was linked to an improvement in cardiovascular and renal structure and function. However, metildopa treatment was associated with some increase in glucose levels and a significant elevation in total cholesterol levels. Conclusion. The complex assessment of cardiometabolic risk factors and target organ status is particularly important for a differential choice of antihypertensive therapy in pregnant women.